“The Answer a Philosopher Gives Determines the Entire Shape of his Metaphysics”: The Influence of Plato and Descartes on Rebecca Goldstein’s The Mind-Body Problem - Sánchez Canales, Gustavo (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2012)
To date, Rebecca Goldstein’s The Mind-Body Problem (1983) has been mostly analysed from two points of view. On the one hand, the significance of Renee Feuer’s Orthodox Jewish background in addressing the/her mind-body problem; on the other, the implications of the Holocaust for Noam’s life and, therefore, for the Noam-Renee relationship. Surprisingly, this novel has not been studied from a purely philosophical perspective. For this reason, the present article attempts to shed some light on the protagonist’s mind-body problem by focusing on the references to René Descartes’ Meditations on First Philosophy (1641) and Plato’s Republic, Book VII.